ANÁLISE DO RELATÓRIO DE SUSTENTABILIDADE DA COOPERATIVA DE CRÉDITO SICREDI, COM ÊNFASE NAS PRÁTICAS SUSTENTÁVEIS DA REGIONAL PLANALTO DAS ÁGUAS - PR/SP - NEVES, ERIKA REGINA TOMEN DAS (2022)
An organization's sustainability report should present its sustainable performance. The objectiveofthepresentstudyistoanalyzethesustainabilitypracticesofthe agencies of the Cooperativa Sicredi Planalto das Águas PR/SP, in view of the need of the Cooperative in to have knowledge of specific details of the region, not perceived in the general report of the Cooperative. The specific objectives are the presentation of the results of an investigation on which strategies and actions are effectively adopted by the Cooperative, within the âmbit of the selected agencies, the indication of points in which the strategies and/or actions that can be improved, and the proposal to prepare a Sustainability Report that includes the regional cooperative Sicredi Planalto das Águas PR/SP, to analyze the sustainability practices of the agencies of Cooperativa Sicredi Planalto das Águas PR/SP, in view of the Cooperative's need to have knowledge of specific details of the region, not perceived in the general report of the Cooperative. Thus, a survey questionnaire wasused to collect data, in the quantitative analysisphase, which weresent to employee selectronically. In the qualitative analysis phase, semi-structured interviews were carried out with the members of the sustainability committee, which were later analyzed through content analysis. The results indicate that the strategies and actions aimed at the sustainability of the local Cooperative are aligned with the Cooperative's national report and also with the ODs. However, some points were identified that need attention, especially some aspects related to the environmental dimension. Finally, it is suggested the implementation of na own report base Don the informationg a there dandon a diagram of the stages of construction and application of the local Sustainability Report for the Cooperativa Sicredi Planalto das Águas PR/SP.